Luminal Plugging on Chest CT Scan: Association With Lung Function, Quality of Life, and COPD Clinical Phenotypes - Okajima, Yuka; Come, Carolyn E; Nardelli, Pietro; Sonavane, Sushil K; Yen, Andrew; Nath, Hrudaya P; Terry, Nina; Grumley, Scott A; Ahmed, Asmaa; Kligerman, Seth; Jacobs, Kathleen; Lynch, David A; et al. (Chest, 2020)
Mucous exudates occluding the lumen of small airways are associated with reduced lung function and mortality in subjects with COPD; however, luminal plugs in large airways have not been widely studied. We aimed to examine the associations of chest CT scan-identified luminal plugging with lung function, health-related quality of life, and COPD phenotypes. We randomly selected 100 smokers without COPD and 400 smokers with COPD from the COPDGene Study. Luminal plugging was visually identified on inspiratory CT scans at baseline and 5-year follow-up. The relationships of luminal plugging to FEV , St. George's Respiratory Questionnaire (SGRQ) score, emphysema on CT scan (defined as the percentage of low attenuation area < 950 Hounsfield units [%LAA-950]), and chronic bronchitis were assessed using linear and logistic multivariable analyses. Overall, 111 subjects (22%) had luminal plugging. The prevalence of luminal plugging was higher in subjects with COPD than those without COPD (25% vs 10%, respectively; P = .001). In subjects with COPD, luminal plugging was significantly associated with FEV % predicted (estimate, -6.1; SE, 2.1; P = .004) and SGRQ score (estimate, 4.9; SE, 2.4; P = .04) in adjusted models. Although luminal plugging was associated with log %LAA-950 (estimate, 0.43; SE, 0.16; P = .007), its relationship with chronic bronchitis did not reach statistical significance (P = .07). Seventy-three percent of subjects with COPD with luminal plugging at baseline had it 5 years later. In subjects with COPD, CT-identified luminal plugging is associated with airflow obstruction, worse health-related quality of life, and emphysema phenotype. This imaging feature may supplement the current clinical assessment of chronic mucus hypersecretion in COPD.